Fenomena Sandwich Generation pada Era Modern Kalangan Mahasiswa: Analisis Fikih Kontemporer - Yeyeng, Andi Tenri; Izzah, Nurul (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The sandwich generation is a condition in which a person has to bear the cost of living and plan his life in the future such as education, health, career, house, vehicle, and marriage. The sandwich generation is required to be able to help support their siblings’ living expenses or pay off debts left by their parents. In addition, they still have to prepare for the cost of necessities, health, and other future costs. According to Islam, meeting the needs of parents is one of the obligations of a child to his parents, providing a happy life, especially if the parents have entered old age. Contemporary Jurisprudence on this issue assumes that living for both parents is obligatory for the child no matter if the child is well off and vice versa. Parents, even with permission or without permission, are allowed to take and manage their children’s assets without being excessive and greedy. But not vice versa with children, a child may not take parental property outside the knowledge and permission of parents.